2019
DOI: 10.1002/mrd.23260
|View full text |Cite
|
Sign up to set email alerts
|

Applications of omics and nanotechnology to improve pig embryo production in vitro

Abstract: An appropriate environment to optimize porcine preimplantation embryo production in vitro is required as genetically modified pigs have become indispensable for biomedical research and agriculture. To provide suitable culture conditions, omics technologies have been applied to elucidate which metabolic substrates and pathways are involved during early developmental processes. Metabolomic profiling and transcriptional analysis comparing in vivo‐ and in vitro‐derived embryos have demonstrated the important role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 145 publications
(304 reference statements)
0
9
0
Order By: Relevance
“…This data shows that lipid nucleic nanoparticles, which have an organogel in their nucleus and acts as a second diffusional barrier for the release of melatonin, increases the protective effects of melatonin against oxidative stress and cell apoptosis during in vitro culture of bovine embryos (Jäger et al, 2009). These studies show the potential of using of nanoparticles in the delivery of different biomolecules during in vitro culture of embryos (Lucas et al, 2019). Komninou et al (2016) reported that bovine embryos cultured in the presence of melatonin-loaded lipid-core nanoparticles had the highest hatching when compared to nonencapsulated melatonin, melatonin-loaded polymeric nanocapsules.…”
Section: Effects Of Nanoparticles On In Vitro Embryo Developmentmentioning
confidence: 62%
See 1 more Smart Citation
“…This data shows that lipid nucleic nanoparticles, which have an organogel in their nucleus and acts as a second diffusional barrier for the release of melatonin, increases the protective effects of melatonin against oxidative stress and cell apoptosis during in vitro culture of bovine embryos (Jäger et al, 2009). These studies show the potential of using of nanoparticles in the delivery of different biomolecules during in vitro culture of embryos (Lucas et al, 2019). Komninou et al (2016) reported that bovine embryos cultured in the presence of melatonin-loaded lipid-core nanoparticles had the highest hatching when compared to nonencapsulated melatonin, melatonin-loaded polymeric nanocapsules.…”
Section: Effects Of Nanoparticles On In Vitro Embryo Developmentmentioning
confidence: 62%
“…This data shows that lipid nucleic nanoparticles, which have an organogel in their nucleus and acts as a second diffusional barrier for the release of melatonin, increases the protective effects of melatonin against oxidative stress and cell apoptosis during in vitro culture of bovine embryos (Jäger et al, 2009). These studies show the potential of using of nanoparticles in the delivery of different biomolecules during in vitro culture of embryos (Lucas et al, 2019).…”
Section: Effects Of Nanoparticles On In Vitro Embryo Developmentmentioning
confidence: 99%
“…Given the importance of genetically modified pigs in biomedical research, an ideal environment for porcine preimplantation embryo development in vitro is required. Interdisciplinary investigations between biology and nanotechnology may solve some problems associated with biological applications, particularly IVP in pigs [ 2 ]. To provide proper culture conditions during IVP, omics technologies are being applied to discover the metabolic substrates that are activated during early embryonic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Nanotechnology is a promising technique owing to its increasing applicability in economically areas, such as agriculture, industry, medicine, and public health [ 1 , 2 ]. Nanotechnology has been applied to improve animal production and health using different approaches [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A significant effect was observed in haptoglobin-incubated blastocyst compared to the control group, and no impairment in blastocyst quality in terms of the total number cells per blastocyst or their size. Several studies have evaluated the supplementation of IVM-IVF-IVC systems with different molecules (reviewed in 30 , 64 ), including natural fluids, such as oviductal fluid 26 , 65 68 or exosomes 69 , finding an increase in the efficiency of IVF and/or the quality of embryos. However, in our study, the percentage of improvement achieved in IVP compared to the control group (haptoglobin: 64.50% vs. control: 37.83%) is one of the greater observed differences 70 75 .…”
Section: Discussionmentioning
confidence: 99%